Latihan Fisik Pada Pasien Obesitas - Oroh, Pricillia J.; Wungow, Herlina I. S.; Engka, Joice N. A. (Jurnal Biomedik : JBM, 2021)
Abstract: Increase in cases of obese patients in developed and developing countries is a problem that occurs from year to year. Prevalence rates of obesity cases has increased in the last 5 years. Prevalence rate of obesity in Indonesia is 21.8%. North Sulawesi is the province with the highest obesity in Indonesia. Obesity can cause many health problems, therefore it takes effort by doing regular physical exercise, in order to increase the body metabolism for obese patients. Purpose of this study is to determine the effect/benefit of physical exercise in obese patients. Material and method used is a literature review with five databases, namely, Clinical Key, PubMed, Science Direct, and Indonesian Scientific Repository. Keywords used are physical activity OR physical training OR exercise program OR exercise therapy OR obesity. Study selection stage obtained 20 literature consisting of 19 randomized controlled trials, and 1 experimental study. Results of the literature review study show that all physical exercise provides benefits to the body, but aerobic physical exercise is mostly done in obese patients. Conclusion: Physical exercise in the form of aerobic exercise, anaerobic exercise, and regular resistance training can provide weight loss, and reduce body fat in obese patients.Key words: physical exercise, physical activity, obesity. Abstrak: Peningkatan kasus pasien obesitas di negara maju, dan negara berkembang merupakan suatu masalah yang terjadi dari tahun ke tahun. Prevalensi kasus obesitas meningkat pada 5 tahun terakhir. Tingkat prevalensi obesitas di Indonesia adalah 21,8%. Sulawesi Utara merupakan provinsi dengan obesitas tertinggi di Indonesia. Obesitas dapat menyebabkan banyak gangguan kesehatan bagi tubuh, maka diperlukan upaya dengan melakukan latihan fisik yang tepat, agar mampu meningkatkan metabolisme tubuh bagi pasien obesitas. Tujuan penelitian adalah untuk mengetahui pengaruh atau manfaat latihan fisik pada pasien obesitas. Materi dan metode penelitian yang digunakan literature review dengan lima database yaitu Clinical Key, PubMed, Science Direct, dan Repositori Ilmiah Indonesia. Kata kunci yang digunakan yaitu physical activity OR physical training OR exercise program OR exercise therapy OR obesity. Tahap seleksi studi didapatkan 20 literatur terdiri dari 19 randomized controlled trial, dan 1 penelitian eksperimental. Hasil penelitian literature review menunjukkan semua latihan fisik memberikan manfaat bagi tubuh, tetapi latihan fisik aerobik paling banyak dilakukan pada pasien obesitas. Kesimpulan: Latihan fisik dalam bentuk latihan aerobik, latihan anaerobik, dan latihan daya tahan yang teratur dapat memberikan penurunan berat badan, dan mengurangi lemak tubuh pada pasien obesitas.Kata kunci: Latihan fisik, aktifitas fisik, obesitas